Students’ Attitudes Towards the Standardisation of the Lithuanian Language - Matulionytė, Akvilė; Jakaitė-Bulbukienė, Kristina (Taikomoji kalbotyra, 2021)
Lithuania’s national language policy has been a frequently discussed topic in the broad Lithuanian society over the recent years. Due to this, it has been made known that Lithuania’s national language policy is an issue that is currently significant to various members of the speech community. Understanding how a speech community views and accepts their country’s national language policy is crucial in developing that policy well and having the community embrace it. The aim of the research presented in this article was to assess Lithuanian students’ attitudes towards the country’s current national language policy and the standard Lithuanian language. A qualitative questionnaire, which 125 respondents participated in, was conducted to reach this aim. The analysis of the students’ language attitudes revealed that they tended to view the standard language as highly prestigious and to associate the use of this language variant with socially admirable cognitive qualities (especially with formal education though preconceptions about the personality qualities of such speakers were differentiated, either negative or positive. The students tended to associate the use of non-standard written language forms (colloquially called ‘language mistakes’) with socially unadmirable cognitive qualities (especially a lack of formal education) though they also tended to normalise it and not express strong negative attitudes towards such persons. The students tended to express neutral attitudes towards the current national Lithuanian language standardisation; however, they also named more negative aspects of the current national standardisation practices than positive ones, mainly centered around a perceived dissonance between standard forms and language forms widely used by the speech community, stagnation of national language standardisation processes, as well as excessive or unfunctional translation of foreign terms. The students’ attitudes towards national language standardisation were found to be positively related to their aesthetic attitudes towards the standard language. Positive attitudes regarding the matter were also more prevalent in female research participants and philology students (especially in students of Lithuanian philology). However, the students that had had experience in professional text editing tended to express more negative attitudes. The research presented in this article may be useful in the efforts to improve Lithuania’s national language policy, as well as in the development of further research on the Lithuanian speech community members’ language attitudes.
Keywords: standard Lithuanian language; language policy; language standardization; linguistic prestige; language attitudes